2019
DOI: 10.1002/bmc.4499
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an analytical method to quantify the permeation and penetration of flurbiprofen into human pharynx tissue

Abstract: The aim of this investigation was to develop receiver and extraction fluids, and subsequently validate an analytical method to quantify the permeation and penetration of flurbiprofen into human pharynx tissue using a Franz diffusion cell. The solubility and stability of flurbiprofen in a suitable receiver fluid, and a suitable extraction method and fluid to recover and quantitate flurbiprofen from human pharynx tissue, were investigated using high‐performance liquid chromatography (HPLC). The potential interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Thus, this ex vivo model was specifically designed to represent a clinical scenario as much as possible. 35 The full-thickness pharynx mucosal tissue consisting of epithelial, basement membrane, and lamina propria from human cadavers was used. This is one of the strengths of this investigation compared with an in vitro synthetic model or other animal tissue; the use of human tissue would match more closely the permeation of flurbiprofen in vivo and the architecture of the pharynx tissue would remain intact.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, this ex vivo model was specifically designed to represent a clinical scenario as much as possible. 35 The full-thickness pharynx mucosal tissue consisting of epithelial, basement membrane, and lamina propria from human cadavers was used. This is one of the strengths of this investigation compared with an in vitro synthetic model or other animal tissue; the use of human tissue would match more closely the permeation of flurbiprofen in vivo and the architecture of the pharynx tissue would remain intact.…”
Section: Discussionmentioning
confidence: 99%
“…Franz diffusion cells were utilized due to their routine application in transdermal drug delivery research/membrane penetration experiments, and the availability of specific methodology using Franz diffusion cells for the quantitation of flurbiprofen penetration through human pharynx tissue. 35 Several studies have shown that flurbiprofen is absorbed across the cells of the buccal mucosa. 29,30 Pharmacokinetic studies show that flurbiprofen is absorbed via the buccal cavity from 1 min 30 and is still detectable in the mouth and oropharyngeal region at 120 mins post dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations